التدفق النفسي لدى طلبة الجامعة - خلوط, رجاء (University of Eloued جامعة الوادي, 2023)
تهدف هذه الدراسة إلى التعرف على التدفق النفسي لدى طلبة الجامعة وبالتحديد جامعة الشهيد حمه لخضر بالوادي، وقد بلغت عينة الدراسة 93 طالبا من مختلف تخصصات علم النفس المدرسي وعلم النفس العيادي وكذا عينة من طلبة سنة أولى وثانية ليسانس، حيث تم اعتماد المنهج الوصفي، واستخدام مقياس التدفق النفسي من اعداد ناصيف2015، حيث صيغت فرضيات الدراسة على النحو الآتي: _ يتمتع طلبة الجامعة بمستوى معتدل من التدفق النفسي. _ توجد فروق ذات دلالة إحصائية في التدفق النفسي تعزى للتخصص والمستوى. وتوصلت الدراسة إلى النتائج الآتية: _ يتمتع طلبة الجامعة بمستوى جيد من التدفق النفسي. _ توجد فروق ذات دلالة إحصائية في التدفق النفسي لدى طلبة جامعة تعزى للمستوى والتخصص. Study Summary in English: This study aims to explore the flow experience among university students, specifically at the University of Shuhada Hamah Lekhdar in El Oued. The study sample consisted of 93 students from various academic disciplines, including school psychology, clinical psychology, as well as a sample of first and second-year undergraduate students. The flow experience scale developed by Nassif (2015) was adopted, based on the Csikszentmhaihalyi theory (1996). The study found several significant results, including the existence of a statistically significant relationship that confirms the presence of flow experience among the students of the University of Shuhada Hamah Lekhdar in El Oued. Moreover, the study revealed differences in the flow experience among students based on their academic disciplines and academic levels.
تخصص علم نفس